The adaptability of school principal and teachers in curriculum design and lesson plan at COVID-19 pandemic - Nurhattati Nurhattati; Desi Rahmawati; Rugaiyah Rugaiyah; Ahmad Jauhari Hamid Ripki; Dirgantara Wicaksono (International Journal of Evaluation and Research in Education (IJERE), 2023)
This research departed from the conditions an Islamic elementary school faces in preparing education planning, especially curriculum design and lesson plan required to adapt to changes, especially in the current pandemic conditions. Therefore, this study aimed to know the adaptability of school principal and teachers in curriculum design and lesson plan during the COVID-19 pandemic. This research used a qualitative approach, while the case study method is used. The data collection process is carried out through observation, interviews, and documentation studies. Then for data validity using triangulation. The data analysis includes data reduction, data display, and conclusion drawing. The subjects of this study were the school principal and the teachers at Al-Istiqlal Islamic elementary school Karawang. The results showed that the COVID-19 pandemic became a momentum for teachers and principals to adapt curriculum design and lesson plan in the 21st century. Various efforts are made in preparing curriculum design, namely making the curriculum essential, compiling learning tools, and preparing digital platforms for teaching and learning activities. The adaptability of school principal in designing curriculum is by creating a primary curriculum. Teachers’ adaptability in making a lesson plan formulated and designed previously by the curriculum team, school principal, and the head of the foundation. It needs to be done because learning activities during the pandemic have changed the learning process and methods; it requires planning for a new curriculum design and lesson plan.